2002
DOI: 10.1038/sj.jhh.1001316
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria, an integrated marker of cardiovascular risk in essential hypertension

Abstract: This paper reviews the existing epidemiological and clinical evidence about the relationships of non-diabetic microalbuminuria with cardiovascular risk factors such as elevated blood pressure (BP), systolic particularly, cardiac hypertrophy, adverse metabolic status, smoking habits, elevated angiotensin II levels, endothelial dysfunction, acute and perhaps subclinical inflammation. Because of that unique property of reflecting the influence of so many clinically relevant parameters, microalbuminuria may legiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
1
16

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 152 publications
5
62
1
16
Order By: Relevance
“…Among factors such as more extensive coronary atherosclerosis in diabetic subjects, alterations in the fibrinolytic system that facilitate reocclusion after fibrinolysis [21,22], diabetic cardiomyopathy with systolic or diastolic dysfunction [23], and autonomic imbalance [24], particular emphasis has been placed on endothelial dysfunction leading to impaired myocardial perfusion [25]. Albuminuria is considered to be a marker of widespread endothelial dysfunction enhancing atherogenesis, and several studies have shown that the mortality risk is 2.3 to 4 times higher in diabetic patients with microalbuminuria than in those without [26,27,28]. Thus, it is possible that the glomerular albumin leak reflects a widespread atherosclerosis-mediated capillary vasculopathy [25,26,27,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among factors such as more extensive coronary atherosclerosis in diabetic subjects, alterations in the fibrinolytic system that facilitate reocclusion after fibrinolysis [21,22], diabetic cardiomyopathy with systolic or diastolic dysfunction [23], and autonomic imbalance [24], particular emphasis has been placed on endothelial dysfunction leading to impaired myocardial perfusion [25]. Albuminuria is considered to be a marker of widespread endothelial dysfunction enhancing atherogenesis, and several studies have shown that the mortality risk is 2.3 to 4 times higher in diabetic patients with microalbuminuria than in those without [26,27,28]. Thus, it is possible that the glomerular albumin leak reflects a widespread atherosclerosis-mediated capillary vasculopathy [25,26,27,29].…”
Section: Discussionmentioning
confidence: 99%
“…Albuminuria is considered to be a marker of widespread endothelial dysfunction enhancing atherogenesis, and several studies have shown that the mortality risk is 2.3 to 4 times higher in diabetic patients with microalbuminuria than in those without [26,27,28]. Thus, it is possible that the glomerular albumin leak reflects a widespread atherosclerosis-mediated capillary vasculopathy [25,26,27,29]. Although we have no ACR values for the patients prior to AMI, it is reasonable to assume that the large difference in ACR between the diabetic AMI group and the diabetic control group is accounted for by AMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Increased urinary albumin excretion (UAE), namely either micro-or macroalbuminuria, is a well-established marker of hypertensive renal target-organ damage (TOD), mainly characterized by glomerular vasculature involvement. 4 An increase in both hsCRP and UAE occurs in a large proportion of nondiabetic essential hypertensive patients, 5 and a strict direct association between high hsCRP levels and increased UAE were found. 6,7 The ultrasound measurement of the renal resistive index (RRI) has been proposed in adjunct to UAE to assess the severity of renal TOD in hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…In our survey, we included the search for microalbuminuria using a dipstick test that measures albumin in the range of 20-200 mg/l. Microalbuminuria has been reported associated with increased cardiovascular risk 2,3 and severity of essential hypertension, but in an extensive review, Bianchi et al 4 quote several studies with controversial results on this association. We explore it here in several thousand people of our national survey.…”
mentioning
confidence: 99%